HfBON nano multilayer composite cutter coating and preparation method thereof

By adding O elements to the HfBN coating to form an HfBON nano multi-layer composite coating, the existing tool coating is solved, and the problem of difficult to meet the high hardness, high temperature oxidation resistance and wear resistance are achieved, and a high-performance coating suitable for high-speed cutting and dry cutting environments is achieved.

CN119824367APending Publication Date: 2025-04-15HUNAN CITY UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202510015562.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

Existing tool coatings are difficult to meet the needs of high hardness, excellent high-temperature oxidation resistance and wear resistance at the same time, especially in processing environments such as high-speed cutting and dry cutting.

Method used

Using coating self-assembly technology and high-power magnetron sputtering technology, O elements are added to the HfBN coating to form an HfBON nano multi-layer composite coating. By alternately depositing HfBON and HfBN single layers, the coating structure is optimized and the high-temperature thermochemical stability and wear resistance of the coating are improved.

Benefits of technology

It achieves high hardness, excellent high-temperature oxidation resistance and wear resistance of the coating, and is suitable for processing environments such as high-speed cutting and dry cutting, reducing the residual stress inside the coating and improving dense performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119824367A_ABST
    Figure CN119824367A_ABST
Patent Text Reader

Abstract

The invention discloses a self-assembled HfBON nano multilayer cutter coating and a preparation method thereof. The coating is prepared by adopting a coating self-assembly technology and a high-power magnetron sputtering technology and comprises an HfBN transition layer, a high-temperature-resistant oxygen-enriched HfBON single layer and a high-hardness nitrogen-enriched HfBN single layer, wherein the HfBON single layer and the high-hardness nitrogen-enriched HfBN single layer are alternately deposited. According to the invention, the self-assembly coating technology is combined with the high-power pulse magnetron sputtering deposition technology, and the element O is added into the HfBN coating with high hardness and toughness, so that the high-temperature thermochemical stability of the coating is improved, and the nano multilayer composite cutter coating with high hardness, toughness, good thermochemical stability and excellent high-temperature wear resistance can be obtained; meanwhile, by adjusting the modulation ratio and the modulation period, the residual stress in the coating can be reduced, and the compactness of the coating is improved; and in addition, the preparation process of the process is simple, and extra cost is not needed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of material surface treatment, and specifically discloses a HfBON nano multilayer composite tool coating and a preparation method thereof. Background Art

[0002] With the rapid development of modern manufacturing industry, the application of difficult-to-process materials is becoming more and more extensive, which poses a more severe challenge to tool performance. Coated tools combine the advantages of high wear resistance, good oxidation resistance and substrate toughness of hard coatings, which significantly improves the cutting performance of tools and reduces processing costs. However, with the development of green processing technology, especially the widespread application of dry cutting technology, tool coatings need to have high hardness and excellent high-temperature oxidation resistance and wear resistance. At present, tool coatings are mainly single-coated, forming tool coatings with a specific function, which is difficult to meet processing requirements. Through the coating self-assembly technology to optimize the coating structure design, combined with high-power pulsed magnetron sputtering technology, O elements are added to the high-hardness and toughness HfBN coating to improve the high-temperature thermochemical stability of the coating, so that tool coatings with excellent high-temperature resistance and wear resistance can be prepared. At the same time, through the optimization design of the multi-layer structure, the internal residual stress of the coating can be reduced, the compactness of the coating structure can be improved, etc., which is one of the important development directions for improving the performance of hard tool coatings. Some nitride tool coatings have appeared. For example, CN107190229A discloses a method for preparing a self-assembled nano-oxynitride high-temperature resistant coating to form an alternating oxygen-rich CrAl(Si)ON / nitrogen-rich CrA(Si)ON coating. It has certain advantages over traditional coated tools in cutting high-temperature alloys, but the coating hardness performance is not particularly outstanding and the wear resistance needs to be improved. Summary of the invention

[0003] In order to solve the above problems, the present invention discloses a HfBON nano multilayer composite tool coating having excellent high temperature oxidation resistance, high wear resistance and high thermal stability and a preparation method thereof.

[0004] The technical solution of the present invention is as follows: The HfBON nano multilayer oxynitride tool coating is prepared by using coating self-assembly technology and high-power magnetron sputtering technology, including: an HfBN transition layer, an alternately deposited HfBON single layer and an HfBN single layer.

[0005] Preferably, the total thickness of the alternately deposited HfBON single layer and HfBN single layer is 1.5-2 μm, and the modulation period of the alternate deposition is 6.0-8.0 nm.

[0006] Preferably, the thicknesses of the HfBON layer and HfBN single layer deposited in the alternating cycle are 3-4 nm and 6-8 nm respectively.

[0007] Preferably, the oxygen content in the HfBON single layer is 10.0-15 at.%.

[0008] Preferably, the thickness of the transition layer is 150-200 nm.

[0009] The preparation method of the HfBON nano-multilayer oxynitride tool coating comprises the following steps: (1) pre-treatment of the cemented carbide substrate before deposition; (2) preheating treatment in a vacuum furnace; (3) bombarding the substrate surface with high-energy Ar ions to remove impurities; (4) depositing an HfBN transition layer; and (5) alternately depositing a high-temperature resistant HfBON single layer and a high-hardness HfBN single layer to form a nano-multilayer oxynitride coating.

[0010] Furthermore, the cemented carbide substrate is a YT14 cemented carbide substrate.

[0011] Furthermore, in step (1), the cemented carbide YT14 substrate deposition pretreatment includes the following steps: the substrate is ultrasonically cleaned with acetone, alcohol, and ionized water for 20 to 30 minutes each, then blown clean with compressed air and fixed on a rotating platform in a vacuum furnace at a rotation speed of 1 to 4 rpm.

[0012] Furthermore, in step (2), the vacuum furnace preheating includes the following steps: before the coating is deposited, the vacuum furnace is heated to 300°C to 400°C, and the background vacuum of the vacuum furnace is pre-evacuated to 1×10-4 Pa.

[0013] Furthermore, in step (3), the high-energy ion bombardment of the surface to remove surface impurities includes the following steps: introducing Ar gas to raise the gas pressure in the furnace to 1.0~2.0 Pa, adjusting the substrate bias voltage to -800~-600 V, and then bombarding the cemented carbide substrate with high-energy Ar ions for 10~15 minutes to remove impurities and oxidation products on the substrate surface; turning on the HfB target, and then adjusting the ion source power to 1.5~3.0 kW, the substrate bias voltage to -800~-1000 V, and performing high-energy ion sputtering to remove the impurities remaining on the cemented carbide substrate again.

[0014] Furthermore, in step (4), the HfBN transition layer deposition includes the following steps: keeping other parameters of step (3) unchanged, reducing the substrate bias voltage to -90~-120V, and reducing the deposition temperature to 300~350°C; then adjusting the N2 gas flow rate to reduce the working gas pressure to 1.0~1.2 Pa, the coating deposition time is 10~20min, and the HfBN transition layer thickness is 150~200nm.

[0015] Furthermore, in step (5), the alternating deposition of the high temperature resistant HfBON single layer and the high hardness HfBN single layer comprises the following steps: starting the HfB target deposition, adjusting the ion source power to 1.5-2.0 kW, introducing nitrogen and oxygen, the nitrogen flow rate is 500 sccm, the oxygen flow rate is 50 sccm, the total flow rate is 550 sccm, the substrate bias voltage is increased to -90-120 V, the deposition time is 100-120 min, the total deposition thickness is 1.5-2 μm, and the modulation period of the alternating deposition is 6.0-8.0 nm.

[0016] Furthermore, in the step (5), the thicknesses of the oxygen-rich HfBON layer and the nitrogen-rich HfBN single layer deposited in alternating cycles are 3-4 nm and 6-8 nm, respectively.

[0017] Based on this, the present invention also provides a cutting tool, comprising the above-mentioned coating.

[0018] The design mechanism of the present invention is as follows: The present invention adds O element into the HfBN coating by self-assembly technology, utilizes O and Hf, B elements to generate HfBON oxynitride layer in the coating, utilizes the excellent high temperature thermal stability and high thermal resistance of the HfBON layer to improve the heat resistance of the coating; the HfBN coating with high hardness and toughness and the HfBON layer with excellent thermochemical stability are alternately deposited to form a nano multi-component composite coating, which can make the HfBON nano multi-component composite coating have the characteristics of significantly excellent single-layer coating, forming a tool coating with good high temperature thermal stability and high wear resistance. High-power magnetron sputtering technology is used to improve the density of the coating structure, reduce the internal defects of the coating, and increase the high temperature oxidation resistance and wear resistance of the coating. Thus, the processing environment requirements such as high-speed cutting and dry cutting are met. In addition, the residual stress inside the coating is reduced by multi-layer structure design, the density of the coating is improved, and the bonding strength between the coating and the cemented carbide substrate is further improved. At the same time, the process preparation process of the present invention is simple and does not require additional costs.

[0019] The advantages of the present invention are as follows: 1. The self-assembled HfBON nano multilayer composite coating prepared by the present invention has the characteristics of high hardness, strong wear resistance and good high-temperature thermochemical stability.

[0020] 2. The HfBON nano multilayer composite coating prepared by the present invention has excellent high temperature wear resistance and is suitable for the field of high-speed cutting. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the principle of the preparation process of the self-assembled HfBON coating process of the present invention and the tool structure; Among them, 0-transition layer (increases membrane-substrate bonding strength), 1-high temperature oxidation resistance layer, 2-high hardness wear-resistant layer; Figure 2 XRD patterns of HfBON nano multilayer coatings with different O contents, HfB target, ion source power of 2.5 kW, nitrogen flow rate of 500 sccm, oxygen flow rate of 50 sccm, total flow rate of 550 sccm, substrate bias voltage of -80 V; Figure 3 The cross-sectional SEM morphology of HfBON nano-multilayer coatings with different O contents: 2.02 at.% (A), 5.47 at.% (B), 9.23 at.% (C), 15.02 at.% (D), 23.06 at.% (E). The current is 80A, the nitrogen flow rate is 500sccm, the oxygen flow rate is 50sccm, the total flow rate is 550sccm, and the substrate bias is -80V; Figure 4 The hardness and elastic modulus of HfBON nano multilayer coatings with different O contents, HfB target, ion source power of 2.5kw, nitrogen flow rate of 500sccm, oxygen flow rate of 50sccm, total flow rate of 550sccm, substrate bias voltage of -80V; Figure 5 The panoramic imaging of scratches on HfBON nano-multilayer coatings with different O contents, HfB target, ion source power of 2.5 kW, nitrogen flow rate of 50 sccm, oxygen flow rate of 50 sccm, total flow rate of 550 sccm, substrate bias voltage of -80 V; Figure 6 Friction coefficient of wear scar of HfBN, HfBON and HfBN / HfBON coatings; (a) Friction coefficient of different coatings at 600°C, (b) Friction coefficient of different coatings at 800°C, HfB target, ion source power of 2.5kw, nitrogen flow rate of 500sccm, oxygen flow rate of 50sccm, total flow rate of 550sccm, substrate bias of -80V. DETAILED DESCRIPTION

[0022] The technical solutions in the implementation cases of the present invention are described clearly and completely below. The described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0023] The reagents or instruments used in the examples of the present invention without indicating the manufacturer are all conventional reagent products that can be obtained through commercial purchase.

[0024] Example 1 Preparation of a HfBON nano multilayer composite tool coating, such as Figure 1 As shown, the self-assembly technology structure optimization design and high-power magnetron sputtering method are used for preparation. When the substrate is located at position ① close to the target source, a nitrogen-rich layer is generated; when the substrate is far away from the target source, an oxygen-rich layer is generated at position ②; by rotating the substrate, nitrogen-rich layers and oxygen-rich layers of nitrogen oxide nano-multilayers are alternately generated to form a nitrogen oxide coating with high hardness, good high-temperature thermal stability and wear resistance; through high-power pulsed magnetron sputtering technology, the comprehensive performance of the coating is improved, and the wear resistance of the coating is further improved.

[0025] The specific steps include: (1) Pretreatment of cemented carbide substrate deposition: The cemented carbide substrate YT14 was ultrasonically cleaned with acetone, alcohol, and ionized water for 20 min each, then blown clean with compressed clean air and placed on a rotating platform in the deposition furnace at a rotation speed of 1 rpm. (2) Preheating of vacuum furnace: Before depositing the coating, heat the vacuum furnace to 400°C and pre-evacuate the vacuum furnace to a vacuum of 1×10 -4 Pa; (3) High-energy ion bombardment to remove impurities: Ar gas was introduced to raise the pressure in the vacuum furnace to 1.0 Pa, and then the substrate bias voltage was adjusted to -400 V. The cemented carbide substrate was cleaned by Ar ion bombardment for 20 min to remove impurities and oxidation products on the surface of the cemented carbide substrate. Subsequently, the HfB target was turned on, the ion source power was adjusted to 1.0 kW, and the substrate bias voltage was -600 V. High-energy ion sputtering was performed to remove the impurities remaining on the cemented carbide substrate again. (4) Deposition of transition layer HfBN: While keeping other parameters unchanged in step (3), the substrate bias voltage was reduced to -90 V, the deposition temperature was reduced to 300 °C, and the ion source power was adjusted to 1.5 kW. Then, the N2 gas pressure and flow rate were adjusted to make the working gas pressure to 1.0 Pa. The deposition time was 15 min, and the thickness of the HfBN transition layer was 100 nm. (5) Alternate deposition of high temperature resistant oxygen-rich HfBON monolayer and high hardness nitrogen-rich HfBN monolayer: Turn on the HfB target for alternating deposition, adjust the ion source power to 2.0 kW, the deposition time to 120 min, the nitrogen flow rate to 500 sccm, the oxygen flow rate to 30 sccm, the total flow rate to 530 sccm, the substrate bias voltage to -90 V, the total deposition thickness to 1.5 μm, and the modulation period of the alternating deposition to 6.0 nm.

[0026] Example 2 A HfBON nano multilayer composite tool coating is prepared by using a self-assembly technology structure optimization design and a high-power magnetron sputtering method, such as Figure 1As shown, the self-assembly technology structure optimization design and high-power magnetron sputtering method are used for preparation. When the substrate is located at position ① close to the target source, a nitrogen-rich layer is generated; when the substrate is far away from the target source, an oxygen-rich layer is generated at position ②; by rotating the substrate, nitrogen-rich layers and oxygen-rich layers of nitrogen oxide nano-multilayers are alternately generated to form a nitrogen oxide coating with high hardness, good high-temperature thermal stability and wear resistance; through high-power pulsed magnetron sputtering technology, the comprehensive performance of the coating is improved, and the wear resistance of the coating is further improved.

[0027] The specific steps include: (1) Pretreatment of cemented carbide substrate deposition: The cemented carbide substrate YT14 was ultrasonically cleaned with acetone, alcohol, and ionized water for 30 min each, then blown clean with compressed clean air and placed on a rotating platform in the deposition furnace with a rotation speed of 2.0 rpm. (2) Preheating of vacuum furnace: Before depositing the coating, heat the vacuum furnace to 450°C and pre-evacuate the vacuum furnace to 1×10 -3 Pa; (3) Surface impurity removal by ion bombardment: Ar gas was introduced to raise the pressure in the vacuum furnace to 2 Pa, and then the substrate bias voltage was adjusted to -500 V. The cemented carbide substrate was cleaned by Ar ion bombardment for 30 min to remove impurities and oxidation products on the surface of the cemented carbide substrate. Subsequently, the HfB target was turned on, the ion source power was adjusted to 1.5 kW, and the substrate bias voltage was adjusted to -800 V. High-energy ion sputtering was performed to remove the impurities remaining on the cemented carbide substrate again. (4) Deposition of transition layer HfBN: Keeping other parameters unchanged in step (3), reduce the substrate bias voltage to -100 V, the deposition temperature to 350°C, and adjust the ion source power to 2.0 kW; then adjust the N2 gas pressure flow rate to make the working gas pressure to 1.2 Pa, the deposition time to 20 min, and the HfBN transition layer thickness to 150 nm; (5) Alternate deposition of high temperature resistant oxygen-rich HfBON monolayer and high hardness nitrogen-rich HfBN monolayer: Turn on HfB target deposition, adjust the ion source power to 2.5 kW, the deposition time to 120 min, the nitrogen flow rate to 550 sccm, the oxygen flow rate to 50 sccm, the total flow rate to 600 sccm, the substrate bias voltage to -100 V, the total deposition thickness to 2 μm, and the modulation period of alternating deposition to 8.0 nm.

[0028] Example 3 A superhard nano multilayer composite tool coating with excellent high temperature resistance and wear resistance is prepared by using self-assembly technology structure optimization design and high-power magnetron sputtering method, such as Figure 1As shown, the self-assembly technology structure optimization design and high-power magnetron sputtering method are used for preparation. When the substrate is located at position ① close to the target source, a nitrogen-rich layer is generated; when the substrate is far away from the target source, an oxygen-rich layer is generated at position ②; by rotating the substrate, nitrogen-rich layers and oxygen-rich layers of nitrogen oxide nano-multilayers are alternately generated to form a nitrogen oxide coating with high hardness, good high-temperature thermal stability and wear resistance; through high-power pulsed magnetron sputtering technology, the comprehensive performance of the coating is improved, and the wear resistance of the coating is further improved.

[0029] The specific steps include: (1) Pretreatment of cemented carbide substrate deposition: The cemented carbide substrate YT14 was ultrasonically cleaned with acetone, alcohol, and ionized water for 45 min each, then blown clean with compressed clean air and placed on a rotating platform in the deposition furnace with a rotation speed of 2.5 rpm. (2) Preheating of vacuum furnace: Before depositing the coating, heat the vacuum furnace to 500°C and pre-evacuate the vacuum furnace to 1×10 -2 Pa; (3) Surface impurity removal by ion bombardment: Ar gas was introduced to raise the pressure in the vacuum furnace to 3 Pa, and then the substrate bias voltage was adjusted to -400 V. The cemented carbide substrate was cleaned by Ar ion bombardment for 45 min to remove impurities and oxidation products on the surface of the cemented carbide substrate. Subsequently, the HfB target was turned on, the ion source power was adjusted to 2 kW, and the substrate bias voltage was adjusted to -1000 V. High-energy ion sputtering was performed to remove the impurities remaining on the cemented carbide substrate again. (4) Deposition of transition layer HfBN: Keeping other parameters unchanged in step (3), the substrate bias voltage was reduced to -100 V, the deposition temperature was reduced to 400 °C, and the ion source power was adjusted to 2.5 kW; then the N2 gas pressure and flow rate were adjusted to make the working gas pressure to 1.5 Pa, the deposition time was 20 min, and the thickness of the HfBN transition layer was 200 nm; (5) Alternate deposition of high-hardness nitrogen-rich HfBN monolayer and high-temperature resistant oxygen-rich HfBON monolayer: Turn on HfB target deposition, adjust the ion source power to 3.0 kW, the deposition time to 100 min, the nitrogen flow rate to 550 sccm, the oxygen flow rate to 70 sccm, the total flow rate to 620 sccm, the substrate bias voltage to -110 V, the total deposition thickness to 2.5 μm, and the modulation period of alternating deposition to 10 nm.

[0030] Performance Testing The superhard nano multilayer composite tool coating prepared in Example 2 was tested, and its structural schematic diagram is shown in the attached figure. Figure 1 shown.

[0031] Coating structure observation: The coating phase structure was studied by XRD. Figure 2As shown in the phase structure diagram, it can be seen that as the O content increases, the phase structure of the multilayer structure remains basically consistent and is composed of a cubic phase, which shows that the self-assembled HfBON multilayer coating maintains structural stability. The coating morphology was observed using SEM, as shown in Figure 3 As shown. Figure 3 (ae) The cross-sectional morphology shows that the multilayer structure makes the coating structure dense and there is no obvious columnar crystal structure. It can be seen that the self-assembled HfBON multilayer coating greatly improves the quality and performance of the coating. In general, when the O content of the HfBON single layer in the coating is 5.47-9.23 at.%, the multilayer composite coating has a dense structure and good stability.

[0032] Coating mechanics, high temperature oxidation performance and tribological performance tests: Nanoindenter was used to test the hardness and elastic modulus of the coating, scratch tester was used to test the coating film-substrate bonding strength, and high temperature friction and wear tester was used to study the tribological properties of the coating in high temperature environment. Figure 4 It can be found that the self-assembled HfBON nano multilayer coating has high hardness when the O content is 9.23 at.%, and its microhardness reaches 36.7 GPa. Figure 5 It can be seen that the self-assembled HfBON nano multilayer coating also significantly improved the coating film-substrate bonding strength. When the O content was between 5.47 at.% and 9.23 at.%, its bonding strength reached more than 80.0N. The friction and wear experiment of the coating also clearly concluded that the HfBON nano multilayer coating also significantly reduced the high-temperature friction coefficient of the coating and improved the high-temperature wear resistance of the coating. At a high temperature of 600°C, the friction coefficient of the self-assembled HfBON nano multilayer coating was reduced to about 0.51, while the average friction coefficients of the HfBON and HfBN single-layer coatings reached 0.58 and 0.68, respectively. Figure 6 (a) As shown. At 800℃, the friction coefficient of the self-assembled HfBON nano-multilayer coating is reduced to about 0.44, while the average friction coefficients of the HfBON and HfBN single-layer coatings reach 0.54 and 0.71, respectively. Figure 6 (c) The wear rate is also greatly reduced at a high temperature of 800°C, as shown in Figure 6 In general, when the B content of the HfBON single layer in the coating is 6.5-10.2 at.%, the multilayer composite coating has high hardness, high bonding strength between coatings, and good wear resistance.

[0033] It can be seen from the above embodiments that (1) the present invention adopts self-assembly coating technology and combines high-power pulsed magnetron sputtering deposition technology to add O element to the HfBN coating to improve the high-temperature thermochemical stability of the coating; through the cross-deposition of high-hardness, strong and tough HfBN layer and high-temperature thermal stability of the HfBON layer, a nano-multilayer composite tool coating with good high-temperature thermochemical stability and excellent wear resistance is obtained. At the same time, by adjusting the modulation period, the internal organizational structure of the coating can be reduced, the density of the coating can be improved, and the comprehensive mechanical properties of the coating can be further improved. (2) The process preparation process of the present invention is simple and does not require additional costs.

[0034] The above-mentioned embodiments only express a limited number of preferred implementations of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. HfBON nano multilayer nitride tool coating, characterized by: The coating is prepared by using coating self-assembly technology and high-power magnetron sputtering technology. The coating comprises: a HfBN transition layer, an alternately deposited HfBON single layer and an HfBN single layer.

2. The HfBON nano multilayer oxynitride tool coating according to claim 1, characterized in that: The total thickness of the alternately deposited HfBON single layer and HfBN single layer is 1.5-2 μm, and the modulation period of the alternate deposition is 6.0-8.0 nm.

3. The HfBON nano multilayer oxynitride tool coating according to claim 2, characterized in that: The thicknesses of the HfBON layer and HfBN single layer deposited in the alternating cycle are 3-4 nm and 6-8 nm, respectively.

4. The HfBON nano multilayer oxynitride tool coating according to claim 1, characterized in that The O content in the HfBON layer is 10.0-15 at.%, the B content is 6.5-10.2 at.%, and the thickness of the transition layer is 150-200 nm.

5. The method for preparing the HfBON nano multilayer oxynitride tool coating according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Pretreatment of cemented carbide substrate before deposition; (2) Preheating in a vacuum furnace; (3) Bombardment of the substrate surface with high-energy Ar ions to remove impurities; (4) Deposition of HfBN transition layer; (5) Alternating deposition of high-temperature resistant HfBON single layer and high-hardness, high-toughness HfBN single layer to form a nano-multilayer nitride oxide coating.

6. The preparation method according to claim 5, characterized in that: In step (1), the cemented carbide substrate deposition pretreatment includes the following steps: the substrate is ultrasonically cleaned with acetone, alcohol, and ionized water for 20 to 30 minutes each, then blown clean with compressed air and placed on a rotating platform in a vacuum furnace and fixed at a rotation speed of 1 to 4 rpm.

7. The preparation method according to claim 5, characterized in that: In step (2), the vacuum furnace preheating treatment includes the following steps: before the coating is deposited, the vacuum furnace is heated to 300°C~400°C, and the background vacuum of the vacuum furnace is pre-evacuated to 1×10-4Pa.

8. The preparation method according to claim 5, characterized in that: In step (3), the high-energy Ar ion bombardment of the surface to remove surface impurities includes the following steps: introducing Ar gas to raise the gas pressure in the furnace to 1.0~2.0 Pa, adjusting the substrate bias voltage to -800~-600 V, and then bombarding the cemented carbide substrate with high-energy Ar ions for 10~15 minutes to remove impurities and oxidation products on the substrate surface; turning on the HfB target, and then adjusting the ion source power to 1.5~3.0 kW, the substrate bias voltage to -800~-1000 V, and performing high-energy ion sputtering to remove the impurities remaining on the cemented carbide substrate again.

9. The preparation method according to claim 5, characterized in that: In step (4), the HfBN transition layer deposition includes the following steps: according to the other parameters of step (3) unchanged, the substrate bias voltage is reduced to -90~-120V, and the deposition temperature is reduced to 300~350℃; then the N2 gas flow rate is adjusted to reduce the working gas pressure to 1.0~1.2 Pa, the coating deposition time is 10~20min, and the HfBN transition layer thickness is 150~200nm.

10. The preparation method according to claim 5, characterized in that: In step (5), the alternating deposition of the high temperature resistant HfBON single layer and the high hardness HfBN single layer comprises the following steps: starting the HfB target deposition, adjusting the ion source power to 1.5-2.0 kW, introducing nitrogen and oxygen, the nitrogen flow rate is 500 sccm, the oxygen flow rate is 50 sccm, the total flow rate is 550 sccm, the substrate bias voltage is increased to -120- -90 V, the deposition time is 100-120 min, the total deposition thickness is 1.5-2 μm, and the modulation period of the alternating deposition is 6.0-8.0 nm.

Citation Information

Patent Citations

  • Self-assembled nano oxynitride high-temperature-resisting coating and preparing method thereof

    CN107190229A

  • Multi-element multi-layer nano composite coating and preparation method thereof

    CN114411088A

  • Hard-coating coated tool

    JP2003291007A